Structural properties of GaAs grown on (100) Si substrates by MOCVD - 김용; 김무성; 김현수; 민석기 (ELSEVIER, 1988)
Structural properties (lattice parameters, misorientation, and crystal quality) of 1-5.5 μ m thick GaAs layers grown on exact (100) Si and 3° off-oriented (100) Si substrates have been measured by DCX (double crystal X-ray) diffractometry. The measured lattice constants normal (α⊥) and parallel (α∥) to the interface are 5.6473 ？ and 5.6639-5.6745 ？, respectively; α⊥ does not d epend on the layer thickness, but α∥ depends on the layer thickness in the range 1-5.5 μ m. Except for the case of exact (100) Si substrate, the GaAs [100] direction is between the surface normal and the [100] Si substrate, and the magnitude of the relative tilt between the GaAs and Si [100] directions is about 0.05°. ？ 1988.